2023
DOI: 10.3390/ani13020281
|View full text |Cite
|
Sign up to set email alerts
|

ACADL Promotes the Differentiation of Goat Intramuscular Adipocytes

Abstract: Intramuscular fat (IMF) deposits help improve meat quality such as marbling, juicy, flavor and tenderness. Long-chain acyl-CoA dehydrogenase (ACADL) is a key enzyme for catalyzing fatty acid oxidation, and studies have shown ACADL is involved in the deposition and differentiation of intramuscular adipocytes. However, the effect of ACADL on intramuscular adipocytes differentiation in goats needs further study. In this study, to explore the mechanism of ACADL on the development of goat intramuscular adipocytes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…A previous investigation presented genetic proof that mutations in PCBD1 can lead to the development of early-onset nonautoimmune diabetes, which exhibits characteristics resembling dominantly inherited HNF1A-diabetes ( Simaite et al, 2014 ). The activation of the TNF signaling pathway is facilitated by ACADL, leading to the promotion of intramuscular adipocyte differentiation ( Li et al, 2023 ). ACADL deficiency pronounced hypoglycemia, accumulation of lipids, elevated levels of free fatty acids in the bloodstream, and impaired insulin sensitivity in the liver ( Zhang et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous investigation presented genetic proof that mutations in PCBD1 can lead to the development of early-onset nonautoimmune diabetes, which exhibits characteristics resembling dominantly inherited HNF1A-diabetes ( Simaite et al, 2014 ). The activation of the TNF signaling pathway is facilitated by ACADL, leading to the promotion of intramuscular adipocyte differentiation ( Li et al, 2023 ). ACADL deficiency pronounced hypoglycemia, accumulation of lipids, elevated levels of free fatty acids in the bloodstream, and impaired insulin sensitivity in the liver ( Zhang et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that ACADL, ACADM, and CPT2 were closely related, and all of them were at important PPI nodes. Long-chain acyl-CoA dehydrogenase (ACADL) is involved in the β-oxidation of long-chain fatty acids [ 30 , 31 ]. Medium-chain acyl-CoA dehydrogenase (ACADM) is involved in the β-oxidation process of medium-chain fatty acids and amino acids [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“… 22 Long-chain acyl-coenzyme A dehydrogenase (Acadl) is a critical enzyme in the initial step of fatty acid β-oxidation. 23 Peroxisomal β-oxidation involves the processing of various fatty acid substrates, acted upon by two or three distinct acyl-CoA oxidase (Acox) enzymes exhibiting varying specificities. 24 Eukaryotes also employ peroxisomal β-oxidation, catalyzed by acyl-CoA oxidase (Acox), instead of Acad proteins.…”
Section: Introductionmentioning
confidence: 99%